2014
DOI: 10.3391/bir.2014.3.4.01
|View full text |Cite
|
Sign up to set email alerts
|

First records of American Wolffia columbiana in Europe – Clandestine replacement of native Wolffia arrhiza?

Abstract: Wolffia columbiana is a member of the family Lemnaceae and native to the Americas. In 2013, the first two occurrences of Wolffia columbiana in Europe were found in Germany and the Netherlands. Differentiation between W. columbiana and the rare native W. arrhiza is difficult and a scanning electron microscope (SEM) was used to confirm plant identification. A brief description of both populations of W. columbiana and some identifying characteristics are given. Due to their small size, Wolffia species are easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Counts of stomata using a dissecting microscope suggest that populations of W. columbiana recorded in north-western France had <10 stomata per frond, whereas counts from material from the Gwent, Pevensey and Somerset Levels typically had (8-)10-20(-25). Schmitz et al (2014) using SEM noted that counts from German populations found 3-14 stomata per frond (mean 5.5) and Dutch populations 3-11 per frond (mean 6.4). Landolt (1986) notes that "In Florida, there are clones of W. columbiana which have up to 30 stomata and therefore resemble W. arrhiza".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Counts of stomata using a dissecting microscope suggest that populations of W. columbiana recorded in north-western France had <10 stomata per frond, whereas counts from material from the Gwent, Pevensey and Somerset Levels typically had (8-)10-20(-25). Schmitz et al (2014) using SEM noted that counts from German populations found 3-14 stomata per frond (mean 5.5) and Dutch populations 3-11 per frond (mean 6.4). Landolt (1986) notes that "In Florida, there are clones of W. columbiana which have up to 30 stomata and therefore resemble W. arrhiza".…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of a photosynthetic upper part which is green and opaque, below which there is an expanded lower layer which is firm and may be green or colourless. Landolt, 1986;Landolt, 1994;Landolt, 2000;Bog et al, 2020) Character W. arrhiza W. australiana W. columbiana W. globosa Species of Wolffia can be very difficult to identify, particularly as counting stomata appears to be unreliable without recourse to Scanning Electron Microscopy (SEM) (Schmitz et al, 2014;W. van der Wen pers.…”
Section: Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hartog & Plas (Au), W. globosa (Roxb.) Hartog & Plas (As) (Sell, Murrell, 1996;Mesterhá et al, 2007;Banaszek, Musial, 2009;Misud, 2010;Iberite et al, 2011;Schmitz et al, 2014;Kirjakov, Velichkova, 2016;Feráková, Onderíková, 1998;Hendrickx, Verloove, 2019;Lecron et al, 2021;Niebler et al, 2021;Lansdown et al, 2022); на Близькому Сході були виявлені Landoltia punctata (G. Mey.)…”
unclassified